3D multislab, multishot acquisition for fast, whole‐brain MR elastography with high signal‐to‐noise efficiency. Issue 2 (17th December 2013) - Johnson, Curtis L.; Holtrop, Joseph L.; McGarry, Matthew D.J.; Weaver, John B.; Paulsen, Keith D.; Georgiadis, John G.; Sutton, Bradley P.
<x xml:space="preserve">Abstract</x> Purpose To develop an acquisition scheme for generating MR elastography (MRE) displacement data with whole‐brain coverage, high spatial resolution, and adequate signal‐to‐noise ratio (SNR) in a short scan time. Theory and Methods A 3D multislab, multishot acquisition for whole‐brain MRE with 2.0 mm isotropic spatial resolution is proposed. The multislab approach allowed for the use of short repetition time to achieve very high SNR efficiency. High SNR efficiency allowed for a reduced acquisition time of only 6 min while the minimum SNR needed for inversion was maintained. Results The mechanical property maps estimated from whole‐brain displacement data with nonlinear inversion (NLI) demonstrated excellent agreement with neuroanatomical features, including the cerebellum and brainstem. A comparison with an equivalent 2D acquisition illustrated the improvement in SNR efficiency of the 3D multislab acquisition. The flexibility afforded by the high SNR efficiency allowed for higher resolution with a 1.6 mm isotropic voxel size, which generated higher estimates of brainstem stiffness compared with the 2.0 mm isotropic acquisition. Conclusion The acquisition presented allows for the capture of whole‐brain MRE displacement data in a short scan time, and may be used to generate local mechanical property estimates of neuroanatomical features throughout the brain. Magn Reson Med 71:477–485, 2014. © 2013 Wiley Periodicals, Inc.